Growth strategies for liner companies in the time of economic recession - Ng, Bernice Si Jia. (2010)
There is plethora of literatures and studies on growth strategies during a recession. Yet this is clearly not evident for topics concerning growth strategies in the Liner container industry, either by virtue of its unique attributes or just a lack in interest by researchers. Otherwise, this basic research paper aims fill this literature gap and intimately examines growth strategies applicable during the recession and explain any trends, if applicable.